DETERMINANT FACTOR THAT INFLUENCED ANXIETY LEVEL AND ENERGY INTAKE AMONG ELDERLY - Ninna Rohmawati (UPT Penerbitan Universitas Jember, 2016)
Demographic changes structure was caused by elderly population increase through decrease number of morbidity and mortality. Indonesia has already turned to a country with aging population since the percentage of elderly population has already reached more than 7%. Specialized of Yogyakarta province with highest percentage of elderly in Indonesia, which was 14.02% in 2009. Choosing of food is a multidimensional behavior, affected by many factors, including psychological measures. Psychological factors such as anxiety, depression, and dementia have significant contributions in determining energy intake. In Indonesia, prevalence of anxiety in elderly was 34.92%. This research was aim to determine determinant factor that influenced anxiety level and energy intake among elderly in Yogyakarta municipality.This research was an analytic observational by using cross sectional study design. Total sample were 214 respondens. Technique of sample using multistage random sampling. Data were analyzed with chi square test and multiple logistic regression. Result showed that most dominant factor that influenced anxiety level was sex. Female elderly had 3.37 times higher risk to experience moderate anxiety level as compare to male elderly. A percentage of 67% female elderly experienced moderate anxiety level consumed fat and oils, and a 83% of them consumed cereals, tubers, and their manufactured products. A percentage of 26.2% subjects had moderate anxiety level. In groups of subjects with moderate anxiety level, intake of energy was mostly excessive.Most dominant factor that influenced anxiety level was sex. In groups of subjects with moderate anxiety level, intake of energy was mostly excessive.